Exploratory study evaluating the relationships between perinatal adversity, oxidative stress, and infant neurodevelopment across the first year of life. - Kameelah Gateau; Lisa Schlueter; Lara J Pierce; Barbara Thompson; Alma Gharib; Ramon A Durazo-Arvizu; Charles A Nelson; Pat Levitt (Public Library of Science (PLoS), 2023)
Early childhood adversity increases risk for negative lifelong impacts on health and wellbeing. Identifying the risk factors and the associated biological adaptations early in life is critical to develop scalable early screening tools and interventions. Currently, there are limited, reliable early childhood adversity measures that can be deployed prospectively, at scale, to assess risk in pediatric settings. The goal of this two-site longitudinal study was to determine if the gold standard measure of oxidative stress, F2-Isoprostanes, is potentially a reliable measure of a physiological response to adversity of the infant and mother. The study evaluated the independent relationships between F2-Isoprostanes, perinatal adversity and infant neurocognitive development. The study included mother-infant dyads born >36 weeks' gestation. Maternal demographic information and mental health assessments were utilized to generate a perinatal cumulative risk score. Infants' development was assessed at 6 and 12 months and both mothers and infants were assayed for F2-isoprostane levels in blood and urine, respectively. Statistical analysis revealed that cumulative risk scores correlated with higher maternal (p = 0.01) and infant (p = 0.05) F2-isoprostane levels at 6 months. Infant F2-isoprostane measures at 2 months were negatively associated with Mullen Scales of Early Learning Composite scores at 12 months (p = 0.04). Lastly, higher cumulative risk scores predicted higher average maternal F2-isoprostane levels across the 1-year study time period (p = 0.04). The relationship between perinatal cumulative risk scores and higher maternal and infant F2-isoprostanes at 6 months may reflect an oxidative stress status that informs a sensitive period in which a biomarker can be utilized prospectively to reveal the physiological impact of early adversity.